Smac mimetic LCL161 overcomes protective ER stress induced by obatoclax, synergistically causing cell death in multiple myeloma - Ramakrishnan, Vijay; Gomez, Marcus; Prasad, Vivek; Kimlinger, Teresa; Painuly, Utkarsh; Mukhopadhyay, Bedabrata; Haug, Jessica; Bi, Lintao; Rajkumar, S Vincent; Kumar, Shaji (Oncotarget, 2016)
Bcl2 and IAP families are anti-apoptotic proteins deregulated in multiple myeloma (MM) cells. Pharmacological inhibition of each of these families has shown significant activity only in subgroups of MM patients. Here, we have examined a broad-spectrum Bcl2 family inhibitor Obatoclax (OBX) in combination with a Smac mimetic LCL161 in MM cell lines and patient cells. LCL161/OBX combination induced synergistic cytotoxicity and anti-proliferative effects on a broad range of human MM cell lines. The cytotoxicity was mediated through inhibition of the IAPs, activation of caspases and up regulation of the pro-apoptotic proteins Bid, Bim, Puma and Noxa by the drug combination. In addition, we observed that OBX caused ER stress and activated the Unfolded Protein Response (UPR) leading to drug resistance. LCL161, however inhibited spliced Xbp-1, a pro-survival factor. In addition, we observed that OBX increased GRP78 localization to the cell surface, which then induced PI3K dependent Akt activation and resistance to cell death. LCL161 was able to block OBX induced Akt activation contributing to synergistic cell death. Our results support clinical evaluation of this combination strategy in relapsed refractory MM patients.
Keywords: fosfatidylinositol-3-kinasy; down regulace; GRP78; Pyrroles; proteiny regulující apoptózu; intracelulární signální peptidy a proteiny; Unfolded Protein Response; protinádorové látky; Up-Regulation; chaperon endoplazmatického retikula BiP; lokální recidiva nádoru; Antineoplastic Combined Chemotherapy Protocols; Cell Line, Tumor; indoly; fosforylace; Phosphorylation; chemorezistence; protoonkogenní proteiny c-akt; upregulace; Intracellular Signaling Peptides and Proteins; Apoptosis Regulatory Proteins; Proto-Oncogene Proteins c-akt; Multiple Myeloma; Heat-Shock Proteins; Phosphatidylinositol 3-Kinases; Bcl-2; Drug Synergism; signální dráha UPR; pyrroly; mitochondriální proteiny; Thiazoles; synergismus léků; Caspases; stres endoplazmatického retikula; Mitochondrial Proteins; IAP; kaspasy; Neoplasm Recurrence, Local; thiazoly; X-Box Binding Protein 1; Endoplasmic Reticulum Chaperone BiP; XBP1; Down-Regulation; lidé; Humans; Indoles; protokoly protinádorové kombinované chemoterapie; apoptóza; protoonkogenní proteiny c-bcl-2; apoptosis; Proto-Oncogene Proteins c-bcl-2; Drug Resistance, Neoplasm; Endoplasmic Reticulum Stress; nádorové buněčné linie; myeloma; mnohočetný myelom; Apoptosis; Antineoplastic Agents; proteiny teplotního šoku